Pembelajaran IPA Berbasis Mind Mapping dalam Pengembangan Kemampuan Berpikir Kritis, Kreatif, Komunikatif, dan Kolaboratif - Minarti Taib (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2021)
Mind mapping based learning is learning to use keyword, terms, images/symbols, describing the integrity of a material. This learning can encourage students to develop thinking technique in all directions, remembering, taking notes, increasing motivation and being able to deduce the results well. The ability of students to think critically and creatively, communicate and collaborate are abilities that must be developed from an early age to enter global competition. This paper aims to describe the science based on mind mapping in developing critical thinking, creative, communicative, and collaborative skills; as well as knowing the development of critical thinking, creative, communicative, and collaborative skills through mind mapping science learning. The form of research is classroom action research carried in 2 cycles using non-test instrument namely observation and interview sheets. The data obtained were processed descriptively using percentage analysis. Based on the results of data analysis, mind mapping based learning can arouse motivation and interest in learning, communicating and collaborating, more constructing knowledge, learning easier. Mind mapping based science learning can develop critical and creative thinking skills respectively by 35%, communicative 40%, and collaborative by 35%.